Transforming Conventional Teaching Materials Towards Creative Learning Media Based on Canva for Education by Pre-Service Teachers - Yasfi Ismayani; Tiara Dwi Saiva; Salman Hafizin (Indonesian Publication Center, 2024)
The transformation of learning media from conventional to digital forms is imperative in facing the Industrial Revolution 5.0 era to improve educational quality. This study aims to analyze the shift in learning media usage from conventional methods, such as chalkboards and printed books which tend to be monotonous, towards the utilization of Canva for Education (CFE) by pre-service teachers. Using the Systematic Literature Review (SLR) method on 10 selected journals from Google Scholar (published 2015-2024), this research evaluates the effectiveness and real impact of using the digital platform. The synthesized results from the reviewed literature indicate significant positive impacts; one empirical study extracted in this review noted that utilizing Canva can increase student learning interest by up to 80%. Furthermore, the literature shows that CFE transforms the teacher's role into a creative learning designer without requiring professional design skills. This transformation provides a positive impact on pre-service teachers in developing interactive, communicative teaching materials that align with modern curriculum needs. Despite challenges such as limited internet infrastructure and digital literacy, the use of CFE proves to be an innovative solution for creating a more meaningful and enjoyable learning experience.